Penerapan Teori Permainan Dalam Menentukan Strategi Pemasaran Batik di Kecamatan Proppo Kabupaten Pamekasan - Mamdudah, Siti; Kuzairi, Kuzairi; Mardianto, M. Fariz Fadillah (Zeta - Math Journal, 2022)
Batik is a form of handicraft that has high artistic value and has become a global Indonesian culture. The expansion of batik products will lead to rapid competition between the batik market, so that batik companies must have an optimal marketing strategy. To find the optimal marketing strategy, this research applies game theory as a direction for optimizing marketing strategy results by collecting data from batik sales through exhibition promotions, online and personal selling. The results showed that the optimal strategy at the Mj-Abe Store lies in the second strategy, namely personal selling promotion. The optimal strategy for Ragiel Batik Stores lies in the third strategy, namely personal selling promotion. The optimal strategy for Toko Kurnia Batik lies in the first strategy, namely exhibition promotion. Finally, the optimal strategy for the Bintang Abadi Store lies in the first strategy, namely exhibition promotion.